Maternal Diabetes Impairs Insulin and IGF-1 Receptor Expression and Signaling in Human Placenta - Tumminia, Andrea; Scalisi, Nunzio M.; Milluzzo, Agostino; Ettore, Giuseppe; Vigneri, Riccardo; Sciacca, Laura (Frontiers in Endocrinology, 2021)
Maternal high blood glucose during pregnancy increases the risk for both maternal and fetal adverse outcomes. The mechanisms underlying the regulator effects of hyperglycemia on placental development and growth have never been well clarified yet. The placenta expresses high amounts of both insulin receptor (IR) and insulin-like growth factor receptor (IGF-1R). The placenta of diabetic women has structural and functional alterations and the insulin/IGF system is likely to play a role in these changes. Aim of the present study was to measure the content of IR and IGF-1R and their phosphorylation in the placenta of women with type 1 diabetes mellitus (T1D) or with gestational diabetes mellitus (GDM) compared to women with normal glucose tolerance (NGT). Placental tissues were obtained from 80 Caucasian women with a singleton pregnancy. In particular, we collected placenta samples from 20 T1D patients, 20 GDM patients and 40 NGT women. Patients were also subdivided on the basis of peripartum glycemia either ≥90 or <90 mg/dl, regardless of the diagnosis. In T1D patients, a higher rate of adverse outcomes was observed. Compared to the GDM women, T1D ones showed a significantly higher average capillary blood glucose levels at the third-trimester of pregnancy and at peripartum, and a higher third-trimester HbA1c values. In both T1D and GDM women HbA1c values during pregnancy correlated with glucose values in the peripartum period (R-squared 0.14, p=0.02). A positive correlation was observed between phosphorylation of placental IR and the glucose levels during the third-trimester of GDM and T1D pregnancy (R-squared 0.21, p=0.003). In the placenta of T1D patients, compared to the NGT women, IGF-1R phosphorylation and IR isoform A (IR-A) expression were significantly increased. Moreover, IGF-1R phosphorylation was significantly increased in the placenta of patients with peripartum glucose >90 mg/dl, and IR-A expression was increased in those with peripartum glucose higher than 120 mg/dl (p=0.046). To the best of our knowledge, our study represents the first one in which an increased maternal blood glucose level during pregnancy is associated with and the increased IGF-1R phosphorylation and increased IR-A expression in the placenta. Both these mechanisms can promote an excessive fetal growth.